Assessing the Capabilities of a New Linear Inversion Method for Quantitative Microwave Imaging - Loreto Di Donato; Roberta Palmeri; Gino Sorbello; Tommaso Isernia; Lorenzo Crocco (International Journal of Antennas and Propagation)
We investigate the imaging capabilities of a new linear microwave imaging approach, which allows to quantitative retrieve the complex permittivity distribution of unknown nonweak targets. To this end, we carry out a parametric numerical analysis for a canonical scatterer (a homogeneous dielectric cylinder with circular cross section) and derive a quantitative criterion to foresee the method’s applicability. The reliability of the criterion is then tested against noncanonical scatterers to show the effectiveness of the method in imaging nonweak targets and in outperforming the linearized inversion method based on the standard Born approximation.